Influence of the addition of rosemary (Rosmarinus officinalis l.) and oregano (Origanum vulgare) on the lipid stability, texture and sensory characteristics of pork burgers - Marins, Annecler Rech de (2021)
There is concern about the toxicity of chemical antioxidants and the increase in their consumption, since the incorporation of antioxidants into foods has increased in recent years due to the need to increase the shelf life of foods. Thus, the objective of this work was to develop different hamburger formulations using pork with the addition of rosemary and oregano spices as a source of natural antioxidants, replacing the synthetic BHT (butyl-hydroxy-toluene). The following parameters were evaluated: color, yield and shrinkage percentage, lipid stability, instrumental texture and sensory analysis through the acceptance test. The results of the color parameters showed differences between the formulations due to the fact that the spices have a dark green color. The cooking yield values found were better compared to other studies, whereas the shrinkage values did not show a significant difference. Spices as a source of antioxidants and the synthetic antioxidant when analyzed individually and also when combined had an effect on specific extinction, BHT had the greatest protective effect against oxidation under analysis at 232 nm and at 270 nm, but oregano stood out at 270 nm showing an effect close to that of the synthetic antioxidant.